Evaluasi Tugas Pokok dan Fungsi Sekretaris Dewan Perwakilan Rakyat Daerah Kabupaten Kuantan Singingi - Irawan, Alji Mailadi; M, Sarjan; Muharam, Sahri; Andri, Alsar; Ramadhanti, Rika; Risvandi, Risvandi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
The duties and functions of the Secretary of the Regional People's Representative Council of Kuantan Singingi Regency are to organize secretarial and financial administration, support the implementation of the duties and functions of the Regional People's Representative Council and improve the performance of the State Civil Apparatus, administrative development of the State Civil Apparatus and public welfare as well as administrative services. These main duties and functions must be carried out by the Secretary of the Regional People's Representative Council of Kuantan Singingi Regency in order to realize the organizational goals that have been outlined or determined so that an organization can be effective. The purpose of the study was to determine how the implementation of the main duties and functions of the Secretary of the Regional People's Representative Council of Kuantan Singingi Regency. The descriptive quantitative research method, using ranking analysis (summarizing scale). The results of the study showed that the main duties and functions of the Secretary of the Regional People's Representative Council of Kuantan Singingi Regency were quite good with a percentage of 3.37%.